Mitochondrial RNA polymerase of Saccharomyces cerevisiae: composition and mechanism of promoter recognition. - Schinkel, A H (1988)
Mitochondrial RNA polymerase of Saccharomyces cerevisiae consists of two different proteins: a core RNA polymerase of 145 kd and a specificity factor of 43 kd, which contributes the capacity to recognize promoters of the various genes encoded in the mitochondrial genome. We purified both components by SDS-PAGE, followed by renaturation to the active state. The two components were used either singly or in combination to study their interactions with promoter-containing DNA fragments. The core component showed random and weak interaction with DNA, the specificity factor none at all, whereas both components together specifically bound to a promoter. In DNase I footprinting experiments, promoter-bound RNA polymerase protected a short region of DNA flanked by hypersensitivity sites and centred around the position at which RNA synthesis starts. The initial phase of transcription gave rise to specific changes in this footprint: the upstream border remained at the same position up to synthesis of a 4-nt RNA chain, whereas at the downstream border progressive disappearance of hypersensitivity sites took place.